Image Processing Based on Partial Differential Equations [electronic book]: Proceedings of the International Conference on PDE-Based Image Processing and Related Inverse Problems, CMA, Oslo, August 8-12, 2005 - Tai, Xue-Cheng (Berlin, Heidelberg : Springer-Verlag Berlin Heidelberg, 2007)
PSZJBL